Upaya Meningkatkan Kemampuan Mengajar Guru Melalui Pelaksanaan Supervisi Kepala Madrasah Di MTs Swasta Yaspen Muslim Tanjung Pura - Agustina Anjayan, Syarifah, Marhan Hasibuan (Cybernetics: Journal Educational Research and Social Studies, 2022)
Agustina Anjayani. Research title: Principal Leadership Model in Improving Teacher Pedagogic Competence in State Elementary Schools Yaspen Muslim. Problem formulation: How is the principal's leadership model at MTs Swasta Yaspen Muslim? How is the pedagogic competence of teachers in carrying out teaching activities at MTs Swasta Yaspen Muslim?. How is the principal's leadership model in improving the pedagogic competence of teachers at MTs Swasta Yaspen Muslim?. The problems found in the research location are: The unavailability of information and technology-based learning media using the internet network so that teaching and learning activities still rely on conventional methods. The conclusions in this study are the leadership model used by the principal of the State Elementary School Yaspen Muslim, namely a persuasive approach, namely the principal of the State Elementary School Yaspen Muslim leading with more familiar techniques and guiding teachers in improving pedagogic competence through concrete examples. So that learning and teaching activities in the midst of the COVID-19 pandemic can still run effectively and efficiently.